Nonalcoholic Steatohepatitis (NASH) and Atherosclerosis: Explaining Their Pathophysiology, Association and the Role of Incretin-Based Drugs - Eleftheria Galatou; Elena Mourelatou; Sophia Hatziantoniou; Ioannis S. Vizirianakis (MDPI AG, 2022)
Nonalcoholic steatohepatitis (NASH) is the most severe manifestation of nonalcoholic fatty liver disease (NAFLD), a common complication of type 2 diabetes, and may lead to cirrhosis and hepatocellular carcinoma. Oxidative stress and liver cell damage are the major triggers of the severe hepatic inflammation that characterizes NASH, which is highly correlated with atherosclerosis and coronary artery disease. Regarding drug therapy, research on the role of GLP-1 analogues and DPP4 inhibitors, novel classes of antidiabetic drugs, is growing. In this review, we outline the association between NASH and atherosclerosis, the underlying molecular mechanisms, and the effects of incretin-based drugs, especially GLP-1 RAs, for the therapeutic management of these conditions.